“Black People, White Hearts”: Origin, Race, and Colour in Contemporary Yemen - Luca Nevola (Antropologia)
The so-called akhdam (servants) or muhammashin (marginalized) are a minority group of black slum dwellers, often associated with impure tasks. Living on the margins of Yemeni society, they claim to be victims of ʿunsuriyya (racism) due to the colour of their skin. Drawing on extensive fieldwork in the governorate of Sanaa, this article aims to place the case of the akhdam in the wider context of an historical discourse on race, genealogy and colour. Focusing on the notion of aṣl (origin), it explores local understandings of “genealogical essentialism”: the belief that moral and physical characteristics pass down lines of descent. By contrasting the case of another Yemeni low status group, the white-skinned beny al-khumus, with that of the black-skinned akhdam, the article expands the notion of racism beyond the boundaries of colour and phenotype, implying an exclusion of the Other based on his patrilineal line of descent. Concurrently, it depicts race as an instrument of self-essentialization for the akhdam, a tool for political struggle.